2022
DOI: 10.2147/ijgm.s384706
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Value of Systemic Inflammatory Response Index and Inflammatory Prognosis Index in Predicting 3-Month Outcome in Acute Ischemic Stroke Patients with Intravenous Thrombolysis

Abstract: Purpose Systemic inflammatory response index (SIRI) was an independent predictor of the prognosis of many diseases. Inflammatory prognostic index (IPI) was a new inflammatory prognostic marker with certain clinical significance. We aimed to explore the association between SIRI, IPI and early stage severity of stroke as well as 3-month outcome of AIS patients. Patients and Methods A total of 63 AIS patients who treated with alteplase were selected. The patients were divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The 22 studies included in this systematic review and meta-analysis were published between 2020 and 2023. Among them, 5 articles were prospective studies [ 25 , 29 , 31 , 33 , 42 ], and the remaining 17 articles [ 9 , 10 , 14 16 , 24 , 26 28 , 30 , 32 , 34 , 36 – 39 , 41 ] were retrospective studies. The studies were conducted in China ( n = 19, two studies were from the MIMIC database), Italy ( n = 1), and Korea ( n = 2), with a total of 12,931 patients included.…”
Section: Resultsmentioning
confidence: 99%
“…The 22 studies included in this systematic review and meta-analysis were published between 2020 and 2023. Among them, 5 articles were prospective studies [ 25 , 29 , 31 , 33 , 42 ], and the remaining 17 articles [ 9 , 10 , 14 16 , 24 , 26 28 , 30 , 32 , 34 , 36 – 39 , 41 ] were retrospective studies. The studies were conducted in China ( n = 19, two studies were from the MIMIC database), Italy ( n = 1), and Korea ( n = 2), with a total of 12,931 patients included.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we observed that neutrophil count is separately associated with poor neurological outcomes, but lymphocyte count does not have a statistically significant correlation with the outcome. New articles in this regard have investigated novel indices such as the Systemic Inflammatory Response Index and Inflammatory Prognostic Index and have found an association between these indices and the short-term prognosis of AIS 18…”
Section: Discussionmentioning
confidence: 99%
“…New articles in this regard have investigated novel indices such as the Systemic Inflammatory Response Index and Inflammatory Prognostic Index and have found an association between these indices and the short-term prognosis of AIS. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that IPI is related to CRP, NLR, and ALB (IPI=CRP×NLR/ALB). Albumin is the main protein in human blood, which maintains body nutrition and balances colloid osmotic pressure [20]. Albumin has many physiological functions, such as antioxidation, anti-in ammation, inhibition of platelet aggregation, and thrombus formation [21].…”
Section: Discussionmentioning
confidence: 99%